A history of the black people in South Africa to 1795: a critical analysis of nineteenth century South African historiography - Kekana, Ntsatsi Simon (University of the Free State (South Campus), 1989)
Abstract not available
Thesis (Ph.D. (Literature and Philosophy))--University of the Free State, 1989
Keywords: Blacks -- South Africa -- History; South Africa -- Historiography